2021
DOI: 10.3390/cancers13092245
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro and In Vivo Cell Uptake of a Cell-Penetrating Peptide Conjugated with Fluorescent Dyes Having Different Chemical Properties

Abstract: In molecular imaging, a targeting strategy with ligands is widely used because specificity can be significantly improved. In fluorescence imaging based on a targeting strategy, the fluorescent dyes conjugated with ligands may affect the targeting efficiency depending on the chemical properties. Herein, we used a cell-penetrating peptide (CPP) as a ligand with a variety of fluorescent cyanine dye. We investigated in vitro and in vivo cell uptake of the dye-CPP conjugates when cyanine dyes with differing charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The inherent "stickiness" of a cationic heptamethine cyanine dye, such as probe 5, suggests that it is unlikely to exhibit the favorable in vivo biodistribution properties needed for high contrast imaging of living subjects. [38] Even the anionic benzoindolinene probe 7, with two appended sulfonate groups, was highly self-aggregated in the NTR assay solution and the rate of NTR-catalyzed cleavage and concomitant fluorescence "turn on" was unacceptably slow. Many literature studies obviate this type of dye self-aggregation problem by including DMSO in the testing solution, but this strategy had no effect on the self-aggregation of probes 5 and 7 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inherent "stickiness" of a cationic heptamethine cyanine dye, such as probe 5, suggests that it is unlikely to exhibit the favorable in vivo biodistribution properties needed for high contrast imaging of living subjects. [38] Even the anionic benzoindolinene probe 7, with two appended sulfonate groups, was highly self-aggregated in the NTR assay solution and the rate of NTR-catalyzed cleavage and concomitant fluorescence "turn on" was unacceptably slow. Many literature studies obviate this type of dye self-aggregation problem by including DMSO in the testing solution, but this strategy had no effect on the self-aggregation of probes 5 and 7 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…[41] Looking to the future, we expect that the two alkyne groups at each end of probe 9 can be used as conjugation sites for attachment of prosthetic groups that further improve probe NIR fluorescence imaging performance by enabling helpful molecular functions such as cell targeting, cell permeation, or ratiometric signalling. [38] Experimental Section…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 However, solely cy5 also shows cellular uptake, with large intracellular clusters being visible intracellular, as shown in previous studies. 29 This indicates that the cy5 can have an effect on the cellular uptake of the cy5–bound guests. Still, clear differences are observed within the cy5-labelled guest molecules, with UPy–cy5 showing no uptake, and c12–cy5 and chol–cy5 displaying cellular uptake, with the latter one also displaying membrane binding.…”
Section: Resultsmentioning
confidence: 99%
“…Cell-penetrating peptides (CPPs) such as TAT, penetratin and antennapedia are short cationic peptide sequences that can translocate across cell membranes [ 113 , 114 ]. Therefore, a number of studies have demonstrated the utility of CPPs to transport biological cargo into cells in vitro and into tissues in vivo, including oligonucleotide cargo.…”
Section: Optimisation Of Oligonucleotide Methods Of Delivery Into Joint Tissuesmentioning
confidence: 99%